Recruitment strategies and match quality - New evidence from representative linked employer-employee data - Tobias Brändle; Philipp Grunau; Michael Haylock; Patrick Kampkötter (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
In economics, the recruitment process of firms is largely treated as a black box. To shed light on this process, we use new representative linked employer-employee data for German private-sector establishments to explore search, selection and screening activities over the years 2012-2018. We document longitudinal changes in hiring policies and address the heterogeneity across establishments relating to size, ownership, sector, and unobserved heterogeneity. Firms' recruitment strategies have sizeable effects on the composition of worker productivity, worker-firm match quality, the number of open vacancies, as well as expected staffing problems. Finally, we outline potential mechanisms and research gaps for future work, where there is room for more detailed and causal evidence. – – We study oligopolistic competition in product markets where the firms' quantity decisions are delegated to managers. Some firms are commonly owned by shareholders such as index funds whereas the other firms are owned by independent shareholders. Under such an asymmetric ownership structure, the common owners have an incentive to coordinate when designing the manager compensation schemes. This implicit collusion induces a less aggressive output behavior by the coordinated firms and a more aggressive behavior by the noncoordinated firms. The profits of the noncoordinated firms are increasing in the number of coordinated firms. The profits of the coordinated firms exceed the profits without coordination if at least 80 % of the firms are commonly owned - an astonishing resemblance to the merger literature.
urn:nbn:de:bsz:21-dspace-1001193
Keywords: J21; J63; M51; 330; Recruitment; Hiring Policies; Linked Employer-Employee Data; Worker Productivity; Vacancies; Match Quality